The institutional & legal framework for protecting poor communities' access to water supply and sanitation in the Senegal and Volta river basins - Sallah-Phillips, Antoinette (Cranfield University, Cranfield University at Silsoe, 2006)
Water is life. While access to water supply and sanitation facilities is considered as one of the most basic human needs, it is also today considered as a human right. Lack of access to safe, affordable, close and adequate water supply and sanitation facilities remains one of the leading causes of diseases and deaths in the world. There are many reasons for this unacceptable situation. One key characteristic is the inadequate institutional and legal framework for water supply and sanitation provision in place. The aim of this research is to gain an improved understanding of existing frameworks, to see what and how it makes the links between the local, regional, national and international levels for communities to access improved water supply and sanitation facilities. The hypothesis being that a framework which does not provide these linkages can have a negative impact on water supply and sanitation provision for poor communities. The research focuses on the institutional and legal frameworks relating to the Senegal and Volta river basins, in West Africa and their constituent countries, one of which, Ghana, is the focus of a more detailed analysis. The study identified that insufficient attention has been given to the establishment of an overall institutional and legal framework at all levels, and particularly to the establishment of regulatory and enforcement bodies at the local, regional, national and international levels and their inclusion in the formulation of water supply and sanitation policies at all levels. A model institutional and legal framework has been developed as a benchmark against which existing frameworks can be evaluated. It draws out key features extending from the local to the international level. The research argues that governments have a primary role to play in facilitating the provision of water supply and sanitation facilities to communities, in particular the poor.